Theology of Badati: A Constructive Contextual Theology in Hutumury Society According to Stephen B. Bevans - Sinaga, Rouli Retta Trifena; Saimima , Johan Robert; Ruhulessin, John Chr.; Islahuddin (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Various threats of conflict and egoism based on differences in interests can occur in the Hutumuri society. However, the badati inherited by the ancestors and traditional elders, carried out by the people in Hutumuri, has been proven in protecting every member of the local community to maintain the society integration of Hutumuri. Therefore, it is urgent to construct badati theologically as a wise and contextual basis for social relations in Hutumuri society to maintain stability and peace internally in Negeri Hutumuri, Maluku society, Indonesia, as is the aim of this research. The research method used here is qualitative research with descriptive analysis of data collected through observation, interviews with traditional and religious leaders in Hutumuri, and literature study. With the contextual theological perspective initiated by Stephen B. Bevans, which is in dialogue with the cosmology, badati practices of the Hutumuri society, along with a study of Galatians 6: 2, the finding of this research is that badati can become a theological source for strengthening society integrity in Hutumuri. Theologically badati is cooperation based on reciprocal hospitality, solidarity, and the fraternal nobility of society. The implication is the strengthening of common life in this nation which needs to be preserved in a sustainable manner.